Optical properties of crzstals GaSe and InSe doped with Cu [Articol] - Evtodiev, Igor; Cuculescu, Elvira; Caraman, Mihail; Anghel, Sergiu; Petrov, M. (My University, 2005)
The anisotropy of absorption spectra in the range of the margin of fundamental band of the crystals GaSe and InSe doped with Cu in the percentage quantities up to 0.5 % at. from which the implementation mechanism of the impurity atoms of Cu in the hexagonal crystal grating of the GaSe and InSe crystals and the localization energy of the impurity levels in the forbidden energetic band is studied.
Keywords: anisotropy of absorption spectra